Recycling agricultural plastic mulch: limitations and opportunities in the United States - Kwabena A. Sarpong; Funmilayo A. Adesina; Lisa W. DeVetter; Kun Zhang; Kevin DeWhitt; Karl R. Englund; Carol Miles (Circular Agricultural Systems)
Plastic mulches have become an essential component of modern agriculture since their introduction in the 1950s. However, disposal of plastic mulches poses serious environmental challenges as plastics that are not considered biodegradable or compostable can take several hundred years to degrade. Each year in the United States, only 9% of overall plastic waste is recycled while 79% is accumulated in landfills or the natural environment. Recycling of plastic mulch is especially constrained due to the contamination that results from their use in farming. Currently, recovered mulches are reported to have 30%–80% surface contamination, primarily from soil and plant debris. Plastic mulch waste is concentrated in areas where they are used and can provide logistical opportunities to the plastic recycling industries. Plastic recycling includes mechanical, advanced (chemical and thermal), and biological methods, that may all be used for polyethylene (PE). Most plastic is recycled using the mechanical method, while advanced and biological methods are promising but face significant financial and technical challenges. For all recycling methods, strategies are needed for managing surface contamination to realize the recycling potential of plastic mulch.